APPLICATION OF ECONOMIC MATHEMATICAL MODELS TO BANKING - Salimov D.T. (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
In a modern market economy, there is a need to increase the competitiveness of enterprises. This requires enterprises to optimally manage their financial resources. Based on this optimal control, the need arises for the effective use of mathematical models. This will be the basis for ensuring optimal operation and growth of the enterprise’s income in the face of uncertainty. The article analyzes the uncertainty between the banking system and their customers using the total probability and Bayesian formulas based on statistical data.